A multi-omics approach to reveal the key evidence of GDF10 as a novel therapeutic biomarker for breast cancer. (2020) - Rahman, Ferdausur; Mahmood, Tousif Bin; Amin, Al; Alam, Rahat; Jharna, Jannatul Ferdous; Samad, Abdus; Ahammad, Foysal
Abstract: Breast cancer (BC) is the most common type of invasive cancer diagnosed in women. It is the second leading cause of death from cancer and the utmost important medical concern women face today. Growth differentiation factor 10 (GDF10) is a member of the transforming growth factor β (TGF-β) superfamily and has been found to play a central role during the growth and differentiation of developing tissues. Recent studies have demonstrated the linkage between GDF10 and different types of cancer. But the relation of GDF10 expression in developing BC has not been established with concrete evidence. Therefore, we performed a multi-omics analysis to evaluate the potentiality of GDF10 as a therapeutic biomarker for human BC. We analyzed the mRNA expression patterns of GDF10 in BC subtypes using Oncomine, GEPIA2, immunohistochemistry, and UALCAN databases. Resultant data obtained from the analysis has provided clear evidence to the downregulation of GDF10 expression in BC subtypes. Additionally, three subsequent missense mutations were identified with a frequency of 0.62%–2.95% copy number alterations in the GDF10 protein sequence by analyzing 16 BCE studies from the cBioPortal database. Furthermore, the Kaplan-Meier plots revealed a positive correlation between the downregulation of GDF10 and the lower survival rate of the BC patients. The co-expressed genes profile of GDF10 was also associated with BC development. ABCA8 has been identified as the most positively co-expressed gene, which was confirmed by correlation analysis using bc-GenExMiner and UCSC Xena server. We also determined different cancer progression pathways mediated by GDF10 and its co-expressed genes by utilizing the Enrichr database. Cumulatively, the outcome data conclude that the down expression of GDF10 is associated with BC progression and patient's survival, which may serve as a therapeutic biomarker for treating BC.